Avaliação do potencial genotóxico de nanopartículas de óxido de zinco e dióxido de titânio pelo ensaio do micronúcleo em células V79 e teste da mancha da asa em Drosophila melanogaster - Reis, Érica de Melo (2014)
The growing exploration of nanoparticles (NPs) engineered structures that have at least one dimension between 1 and 100 nm has a wide range of applications in many fields. The aim of the present study was evaluate the cytotoxic, mutagenic and recombinogenic effects of: 1] Amorphous Zinc oxide (ZnO), used as cement in endodontic; 2] ZnO NPs (21 nm); 3] three different types of Titanium dioxide (TiO2) NPs: anatase TiO2 (5.2 nm), anatase TiO2 (9.1 nm) and rutile TiO2 (55.1 nm). The tests employed were the in vivo wing Somatic Mutation and Recombination Test (SMART) in Drosophila melanogaster wings and the in vitro Cytokinesis-Block Micronucleus (CBMN) assay using Chinese hamster lung fibroblasts (V79 culture cells). D. melanogaster larvae of 72 ± 4 h, obtained from standard cross (ST) or high bioactivation cross (HB) were treated with 1.5625; 3.125; 6.25 or 12.5 mM to perform wing spot test (SMART). From both crosses, were obtained marker transheterozygous (MH) and balancer heterozygous (BH) descendants. The analysis of MH descendants showed that, for all composites, mutagenic and recombinogenic effects were observed only in HB cross. Statistically significant increase in the frequency of mutant spots was observed in individuals treated with 6.25 mM of amorphous ZnO and 12.5 mM of ZnO NPs, mainly due to induction of small single spots. The negative results observed in correspondent BH individuals, in witch is possible the detection only of mutation and chromosomal aberration, allow us to suggest that the increase in the frequency of small single spots observed in MH descendants is mainly due to recombination between flr3 and mwh loci. For TiO2 NPs, anatase of 5.2 nm was mutagenic at concentrations 1.5625 and 3.125 mM, and rutile phase of 55.1 nm significantly increased the frequency of mutant spots at all concentrations tested, except at 3.125 mM. Anatase TiO2 NPs (9.1 nm) did not cause mutagenic effects in wing of D. melanogaster neither in ST nor in HB crosses. The mutagenic effects observed in HB cross in contrast with ST cross in SMART assay can be justified possibly by the increase of metabolic activity in that cross, with an increasing production of reactive oxygen species and consequently higher DNA aggression. To determine the cell treatment for CBMN assay, several concentrations of ZnO NPs and three types of TiO2 NPs, ranging from 30.5 to 62,500.00 μM, were tested for cytotoxic activity by XTT colorimetric assay with xv V79 cells. ZnO NPs (21 nm) and anatase TiO2 NPs (5.2 and 9.1 nm) demonstrated similar cytotoxic intensity, showing decrease of V79 cell viability since concentration 224.1 μM. On the other hand, rutile TiO2 NPs (55.1 nm) cytotoxicity started later, at 7,812.00 μM. Among all NPs assessed, only ZnO (21 nm) and anatase TiO2 (5.2 nm) at highest concentration were able to induce genotoxicity in V79 cells. Both, anatase TiO2 NPs (9.1 nm) and rutile TiO2 NPs (55.1 nm) have not caused significant micronuclei increase. There are several physicochemical parameters that can influence on toxic effects of NPs, what corroborate to differences in cytotoxic and genotoxic patterns. In the experimental conditions performed in this study, we can affirm that both kinds of ZnO, as well, both, anatase and rutile phases of TiO2 NPs, were able to induce mutagenicity. Therefore, the use of these NPs should be closely monitored and its genotoxicity action mechanisms must be elucidated.